Association of IL-4 and IL-10 Polymorphisms With Preterm Birth Susceptibility: A Systematic Review and Meta-Analysis - Cao, Xian-Ling; Zhou, Xuan-You; Xu, Nai-Xin; Chen, Song-Chang; Xu, Chen-Ming (Frontiers in Immunology, 2022)
Objective: Preterm birth (PTB) is considered to be a typical inflammatory disease with unclear pathogenesis. The aim of our study was to summarize the effects of IL-4 and IL-10 gene polymorphism and clarify their possible association with PTB. Methods: A systematic literature search was performed using PubMed, Web of science and the Cochrane library (up to 02 April 2022). The MeSH terms, related entry terms and other names in “Gene” database were used to identify relevant articles. A fixed- or random-effects model was employed according to the heterogeneity among studies to calculate the significance of IL-4 and IL-10 gene polymorphisms. The odds ratios and 95% confidence intervals (CIs) were estimated in the allele model, recessive model, dominant model, co-dominant model and over-dominant model respectively. Eggers publication bias plot was used to visualize the publication bias graphically. Results: A total of 21 articles were analyzed with polymorphisms in two interleukins (IL-4-590C/T (rs2243250) =5 and IL-10-592A/C(rs1800872), -819T/C(rs1800871) and -1082A/G (rs1800896) =16). Overall, significant associations between IL-10-1082A/G (rs1800896) and PTB were identified only from the over-dominant gene model AA+GG vs. AG (OR [95% CI] =0.87[0.76,0.99], P=0.04). However, the polymorphisms for IL-4-590C/T (rs2243250), IL-10-592A/C(rs1800872) and IL-10-819T/C(rs1800871) were not found to be associated with the risk of PTB in both the allele model, recessive model, dominant model, co-dominant model and over-dominant model. In subgroup analyses by racial or control group Hardy-Weinberg Equilibrium (HWE) P-value, no statistically significant association between IL-4-590C/T (rs2243250), IL-10-592A/C (rs1800872), IL-10-819T/C(rs1800871) and IL-10-1082A/G (rs1800896) polymorphism and PTB was identified in both above gene models. Eggers publication bias plot and heterogeneity test(I2＜50%, P=0.05) of IL-10-1082A/G (rs1800896) implied that the asymmetry of funnels might be due to publication bias than heterogeneity. Conclusion: The present study suggests that the over-dominant gene model AA+GG vs. AG of IL-10-1082A/G (rs1800896) polymorphism might be associated with genetic susceptibility to PTB and may have a protective function against PTB risk. No unambiguous association were identified between IL-4-590C/T (rs2243250), IL-10-592A/C (rs1800872) and IL-10-819T/C (rs1800871) polymorphisms and PTB. Future studies are needed to confirm our conclusion due to the limitations of included studies and the risk of publication bias.